Elucidation of the role of glutamine synthetase seed isoform GLN1;5 in Arabidopsis thaliana (L.) with a reverse genetics approach - Dragićević, Milan B.; Ćuković, Katarina B.; Zdravković-Korać, Snežana R.; Simonović, Ana D.; Bogdanović, Milica D.; Todorović, Slađana I. (Archives of Biological Sciences, 2019)
Abstract: Glutamine synthetase (E.C. 6.3.1.2) is a key enzyme of plant nitrogen metabolism that assimilates ammonia into glutamine. The Arabidopsis thaliana genome encodes one chloroplastic (GLN2) and five cytosolic (GLN1;1 – GLN1;5) isoforms with different expression patterns, kinetic properties, regulation and functions. Physiological roles of different isoforms have been elucidated mainly by studying knockout mutants. However, the role of GLN1;5, which is expressed in dry seeds, remains unknown. To clarifty the function of GLN1;5, we studied a GLN1;5 knockout line (GLN1;5KO) homozygous for T-DNA insertion within the GLN1;5. GLN1;5 deficiency results in a phenotype with slightly delayed bolting and fewer siliques. The dry weight of GLN1;5KO seeds was 73.3% of wild-type (WT) seed weight, with seed length 90.9% of WT seeds. Finally, only 18.33% of the mutant seeds germinated in water within 10 days in comparison to 34.67% of WT seeds. KNO3 strongly stimulated germination of both GLN1;5KO and WT seeds, while germination in the presence of increasing NH4Cl concentrations potentiated the differences between the two genotypes. It can be concluded that GLN1;5 activity supports silique development and grain filling and that it has a role in ammonium reassimilation in the seed, as well as assimilation and/or detoxification of ammonium from the environment. https://doi.org/10.2298/ABS190315026D Received: March 15, 2019; Accepted: April 4, 2019; Published online: April 10, 2019 How to cite this article: Dragićević MB, Ćuković KB, Zdravković-Korać SR, Simonović AD, Bogdanović MD, Todorović SI. Elucidation of the role of glutamine synthetase seed isoform GLN1;5 in Arabidopsis thaliana (L.) with a reverse genetics approach. Arch Biol Sci. 2019;71(3):443-53.